Endorsement Power : A Multimodal Analysis On Korean Beauty Product Advertisements In Malaysia - Liaw, June Pei Hua (Universiti Malaysia Sarawak, (UNIMAS), 2017)
This study entitled "Endorsement Power: A Multimodal Analysis on Korean Beauty Product Advertisements in Malaysia" aims. in analysing the Korean beauty product advertisements and identifying the power of endorsement in the advertisements in the views of Korean beauty product consumers. Fifteen Korean beauty product advertisements were analysed using O'Toole's (1994) framework to describe the representational functions by the modes of communication, and short interviews were held to investigate the power of endorsers in consumers' purchase intention of the products. From the analysis, two modes of communication, static images and texts were found. All the advertisements has an image of the endorsers and most of it were K-Pop idols. The most dominant theme found in the advertisement is nature and most advertisements had an outdoor setting. All the advertisements had a goal in captivating the viewers' attention with a few exceptions that had an additional goal of showing the product is based on natural ingredients. The written texts mostly showed the brand name and name of product. Data from the interviews showed that more consumers are attracted to the endorsers in the advertisements. This study can be extended via the use of other functions as stated in O'Toole's (1994) framework.